Does non-erosive rheumatoid arthritis exist? A cross-sectional analysis and a systematic literature review (2015)
Objective: To evaluate the prevalence and factors associated with non-erosive rheumatoid arthritis (RA). Methods: First, a cross-sectional analytical study was performed. Non-erosive disease, defined as the absence of any erosion on X-rays after 5 years of RA, was evaluated in 500 patients. Further and additional evaluations including ultrasonography (US) and computed tomography (CT) were performed in those patients meeting the eligibility criteria. The Spearman correlation coefficient, kappa analysis, and Kendall[U+05F3]s W test were used to analyze the data. Second, a systematic literature review (SLR) was performed following the PRISMA guidelines. Results: Of a total of 40 patients meeting the eligibility criteria for non-erosive RA, eight patients were confirmed to have non-erosive RA by the three methods. A positive correlation between non-erosive RA and shorter disease duration, antinuclear antibodies positivity, lower rheumatoid factor (RF) and C-reactive protein titers, lower global visual analog scale values, toxic exposures, and lower disease activity-(RAPID3) was found. In addition, an inverse correlation with anticyclic citrullinated peptide antibodies (ACPA) positivity and medication use was observed. From the SLR, it was corroborated that factors associated with this subphenotype were shorter disease duration, younger disease onset, negative ACPA and RF titers, low cytokine levels, and some genetic markers. Conclusion: Non-erosive RA is rare, occurring in less than 2% of cases. These findings improve on the understanding of RA patients who present without erosions and are likely to have less severe disease. © 2014 Elsevier Inc.